Focus Groups to Study the Acceptability of Male Circumcision as a Measure to Prevent HIV Infection Among Men Who Have Sex with Men in Thailand - เชมนะสิริ, ธรีรัตน์; เชื้อชูวงศ์, รัตน์; ไชยคำเมา, ศุภพร; อึ้งประเสริฐกุล, พัฒน์นรี; วรางค์รัตน์, อัญชลี; วัน กรีนสแวน, ฟริทส (Disease Control Journal, 2010)
This study investigated the acceptability of male circumcision (MC) as a measure to prevent HIV infection among men who have sex with men (MSM) in Thailand. Six focus group discussions were conducted during November 2007 to February 2008. All 41 participants were recruited. Socio-demographic and sexual behavioral data were collected using a short-questionnaire. Atlas.ti version 4.2 was used in data analysis. It was found that there were 6 barriers to the acceptability of MC as a measure to prevent HIV infection among MSM in Thailand as follows: 1. Participants are concerned about efficacy of MC for HIV prevention, 2. Participants think that benefits of MC might not be worth going through post surgical pain, 3. Participants believe that MC can prevent HIV among MSM who perform insertive role ("top") only during anal sex intercourse, 4. Participants think of MC as a minor surgery for people with phimosis or paraphimosis, as a religious rite, or for personal hygiene, 5. Participants believe that they have other ways to protect themselves from HIV, and 6. Participants are not aware of different circumcision styles. We suggested that appropiate and accurate information of MC should be given to public. MC should be recommended to parents for newborns not only as a HIV preventive tool, but as a general hygienic matter. Condom use campaign should be promoted consistently.